Complex solutions under shear and pressure: a rheometer setup for X‐ray scattering experiments. (24th March 2017) - Wieland, D. C. F.; Zander, T.; Garamus, V. M.; Krywka, C.; Dedinaite, A.; Claesson, P.; Willumeit-Römer, R.
Abstract : Development of a high‐pressure rheometer for in situ X‐ray scattering experiments. Abstract : A newly developed high‐pressure rheometer for in situ X‐ray scattering experiments is described. A commercial rheometer was modified in such a way that X‐ray scattering experiments can be performed under different pressures and shear. First experiments were carried out on hyaluronan, a ubiquitous biopolymer that is important for different functions in the body such as articular joint lubrication. The data hint at a decreased electrostatic interaction at higher pressure, presumably due to the increase of the dielectric constant of water by 3% and the decrease of the free volume at 300 bar.